Analisis Dan Perancangan Sistem Informasi Untuk Meningkatkan Efisiensi Pengelolaan Data Administrasi - Yahfizham Yahfizham; Muhammad Daffa Fahreza (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The application of information systems in the current era of digitalization is very important for data management in a company, both in the government and private sectors. This research aims to analyze and design information systems to improve the efficiency of administrative data management in the Office of the Governor of North Sumatra. With the lack of application of information systems in the Office of the Governor of North Sumatra, this research is important to support administrative processes and data processing efficiency. The research method includes interviews with related parties, observations, and direct surveys to the field to understand the administrative process of the obstacles faced. Furthermore, a website-based information system solution will be proposed that can improve the efficiency, speed and accuracy of administrative data management in the Office of the Governor of North Sumatra. The results of this research are expected to provide an in-depth description of how the implementation of the right information system can optimize administrative data management. The implementation of this solution is expected to provide significant benefits in improving administrative performance and opening up opportunities for further application of information technology in the local government environment.